## blessbails 3 years ago Simplify the expression. (–2 – 2i)(–4 + 6i) >8 – 4i >8 – 12i >20 – 4i >–4 – 4i

1. SheldonEinstein

Do you know the value for i (iota) ?

2. surdawi

just multiply everything and you should get the answer (i*i=-1)

3. UnkleRhaukus

$\quad(–2 – 2i)(–4 + 6i)$ $=-2(–4 + 6i) -2i(-4+6i)$

4. SheldonEinstein

$\large{(-2-2i)(-4+6i)}$ $\large{-2(-4) -2i(-4) -2(6i) -2i(6i)}$ $\large{8 + 8 i - 12 i -12i^2}$

5. surdawi

>–4 – 4i

6. SheldonEinstein

Now since : $\large{ i = \sqrt{-1} }$ Therefore, $\large{i^2 = (\sqrt{-1})^2 = -1 }$

7. SheldonEinstein

Solving this we get : 8 - 4i - 12 = -4-4i

8. SheldonEinstein

Therefore the answer is : >-4-4i

9. blessbails

thank you all so much, i've got it now! @SheldonEinstein @surdawi

10. SheldonEinstein

Nice!

11. UnkleRhaukus

mistake !

12. SheldonEinstein

20 -4i

13. SheldonEinstein

Sorry it will be : $\large{8 + 12 - 4i = 20 -4i}$

14. SheldonEinstein

I am REALLY VERY VERY SORRY for that... Thanks @UnkleRhaukus for pointing it out.

15. UnkleRhaukus

$-12i^2=+12$

16. SheldonEinstein

Yeah